Menanamkan rasa tenggang rasa antar umat beragama di Desa Pemenang Barat, Lombok Barat - Afifurrahman Afifurrahman; Zakaria Zakaria; Muhammad Syawahid (State Islamic University of Mataram, 2023)
Pemenang Barat Village is one of the villages from the Pemenang sub-district which is classified as advanced and developing, marked by one of its livelihoods being obtained from tourism. The village of Pemenang Barat is also a village that adheres to three religions, namely Islam, Hinduism, and Buddhism. These three people from the past have never had friction because they have been bound by the word 'Mempolong' which means the bond of brotherhood. The purpose of this service is to continue to maintain inter-religious harmony in the village of Pemenang Barat, Pemenang sub-district, North Lombok district by conducting the Mempolong Pemenang Conference. The research method that the author uses is the PAR (Participatory action research) method, this method model is that we as researchers are actively involved in finding the problem, finding solutions, and actively participating in activities to overcome these problems. The service participants came up with a solution by uniting activists, religious leaders, and cultural figures in the Conference of Mempolong Pemenang.